The Concept of Teachers as Agents of Change in Education - Nasrul, Nasrul; Ringgit, Awang; Akmal, Fauzi; Mardiana, Puja Dikusuma (Al-kayyis: Journal of Islamic Education, 2024)
A change agent is a person or expert who has the ability to influence clients to make changes as expected. This study aims to describe and understand in depth the strategic function of teachers as agents of change, as well as to evaluate how this role is applied in practice and has a positive impact on learning and school culture. This study uses the Systematic Literature Review method or systematic literature study steps, The initial step is to collect scientific research materials or literature related to educational administration and the fundamentals of organizational development, specifically focusing on the concepts and roles of change agents, also known as Agents of Change, sourced from websites, books, articles, journals, and other sources. After these scientific research materials are collected, the researcher studies and understands them. The research findings indicate that change is a natural occurrence that arises in the course of human life and human civilization. The implication is that innovative learning methods must be in line with the learning objectives set by teachers, capable of achieving what has been planned, have the ability to implement a variety of learning and teaching strategies tailored to the learning interests and needs of students, and be able to improve the quality of the learning process and learning outcomes aimed at improving the overall quality of education.